Tunable charge transfer properties in metal-phthalocyanine heterojunctions. Issue 16 (6th April 2016) - Siles, P. F.; Hahn, T.; Salvan, G.; Knupfer, M.; Zhu, F.; Zahn, D. R. T.; Schmidt, O. G.
Abstract : The transport properties of phthalocyanine heterojunctions are precisely tuned via engineering of the organic heterostructure. Conductive AFM techniques allow identifying transport mechanisms and performing nanoscale spatial mapping of carrier mobility. Abstract : Organic materials such as phthalocyanine-based systems present a great potential for organic device applications due to the possibility of integrating films of different organic materials to create organic heterostructures which combine the electrical capabilities of each material. This opens the possibility to precisely engineer and tune new electrical properties. In particular, similar transition metal phthalocyanines demonstrate hybridization and charge transfer properties which could lead to interesting physical phenomena. Although, when considering device dimensions, a better understanding and control of the tuning of the transport properties still remain in the focus of research. Here, by employing conductive atomic force microscopy techniques, we provide an insight about the nanoscale electrical properties and transport mechanisms of MnPc and fluorinated phthalocyanines such as F16 CuPc and F16 CoPc. We report a transition from typical diode-like transport mechanisms for pure MnPc thin films to space-charge-limited current transport regime (SCLC) for Pc-based heterostructures. The controlled addition of fluorinated phthalocyanine also provides highly uniform and symmetric-polarized transport characteristics with conductance enhancements up to two orders of magnitude depending on the polarization. We present a method to spatially map the mobility of the MnPc/F16 CuPc structures with a nanoscale resolution and provide theoretical calculations to support our experimental findings. This well-controlled nanoscale tuning of the electrical properties for metal transition phthalocyanine junctions stands as key step for future phthalocyanine-based electronic devices, where the low dimension charge transfer, mediated by transition metal atoms could be intrinsically linked to a transfer of magnetic moment or spin.